New‐onset atrial fibrillation and outcomes following isolated coronary artery bypass surgery: A systematic review and meta‐analysis. Issue 9 (21st July 2020) - Kerwin, Matthew; Saado, Jonathan; Pan, Jonathan; Ailawadi, Gorav; Mazimba, Sula; Salerno, Michael; Mehta, Nishaki
Abstract: Prior meta‐analyses have shown that new‐onset atrial fibrillation (NOAF) occurs in up to 40% of patients following cardiac surgery and is associated with substantial major adverse cardiovascular events. The stroke and mortality implications of NOAF in isolated CABG without concomitant valve surgery is not known. We thought that NOAF would be associated with increased risk of stroke and mortality, even in patients undergoing isolated CABG. A blinded review of studies from MEDLINE, CENTRAL, and Web of Science was done by two independent investigators. Stroke, 30‐day/hospital mortality, long‐term cardiovascular mortality, and long‐term (>1 year) all‐cause mortality were analyzed. We used Review Manager Version 5.3 to perform pooled analysis of outcomes. Of 4461 studies identified, 19 studies (n = 129 628) met inclusion criteria. NOAF incidence ranged from 15% to 36%. NOAF was associated with increased risk of stroke (unadjusted OR 2.15 [1.82, 2.53] [ P  < .00001]; adjusted OR 1.88 [1.02, 3.46] [ P = .04]). NOAF was associated with increased 30‐day/hospital mortality (OR 2.35 [1.67, 3.32] [ P  < .00001]) and long‐term cardiovascular mortality (OR 2.04 [1.35, 3.09] [ P = .0007]) NOAF was associated with increased long‐term all‐cause mortality (unadjusted OR 1.79 [1.63, 1.96] [ P  < .00001]; adjusted OR 1.58 [1.24, 2.00] [ P = .0002]). We found that the incidence of NOAF following isolated CABG is high and is associated with increased stroke rate and mortality. Early recognition and management of NOAF could improve outcomes.